KEMUNCULAN YOHANES PEMBAPTIS DALAM LENSA SINOPTIS: SIGNIFIKANSI TEOLOGIS MATIUS, MARKUS, DAN LUKAS - Paulus Dimas Prabowo; Jevri Terok; Luhut Pardomuan Lumban Gaol (Universitas Kristen Immanuel, 2024)
This article was raised because there is a problem of multiple interpretations related to the appearance of John the Baptist in the Synoptic Gospels, where one group believes there are similarities while the other group states that each Synoptic Gospel presents differences. To mediate this problem, the author uses a comparative analysis method on the narrative of the appearance of John the Baptist in Matthew 3:1–12, Mark 1:1–8, and Luke 3:3–9, 15–17. The results show that there are similarities as well as differences between the three. These differences indicate that each writer of the Synoptic Gospels has different theological interests and are used to support the main purpose of writing their respective gospels.